2023
DOI: 10.1055/s-0043-1771467
|View full text |Cite
|
Sign up to set email alerts
|

The Interface between Inflammatory Bowel Disease, Neuroinflammation, and Neurological Disorders

Abstract: Inflammatory Bowel Disease (IBD) is a complex, chronic inflammatory condition affecting the gastrointestinal tract. IBD has been associated with a variety of neurologic manifestations including peripheral nerve involvement, increased risk of thrombotic, demyelinating and events. Furthermore, an evolving association between IBD and neurodegenerative disorders has been recognized, and early data suggests an increased risk of these disorders in patients diagnosed with IBD. The relationship between intestinal infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…Chronic inflammation, damage to the gut mucosa, and immune system dysregulation in IBD can lead to structural and functional alterations within the ENS, therefore potentially altering communication through the GBA (Figure 1B) [23][24][25]. Myenteric plexitis has been reported in a majority of CD (75%) and UC (56%) cases [26].…”
Section: Enteric Nervous System Alterations In Ibdmentioning
confidence: 99%
“…Chronic inflammation, damage to the gut mucosa, and immune system dysregulation in IBD can lead to structural and functional alterations within the ENS, therefore potentially altering communication through the GBA (Figure 1B) [23][24][25]. Myenteric plexitis has been reported in a majority of CD (75%) and UC (56%) cases [26].…”
Section: Enteric Nervous System Alterations In Ibdmentioning
confidence: 99%
“…However, a meta-analysis of cohort studies revealed an increased risk of stroke, all-cause dementia, PD, and MS in IBD patients [ 42 ]. The GBA and gut microbiota dysbiosis are thought to play a role in the association between IBDs and neurodegenerative diseases [ 9 , 43 , 44 , 45 , 46 ].…”
Section: Is Neurodegeneration An Extraintestinal Manifestation Of Ibds?mentioning
confidence: 99%
“… Chronic inflammation is a hallmark of both IBDs and neurodegenerative diseases. Inflammatory mediators and immune cells can cross the BBB and contribute to neuroinflammation, neuronal damage, and neurodegeneration [ 43 , 47 , 48 , 49 ]. Increased oxidative stress, resulting from an imbalance between reactive oxygen species (ROS) production and antioxidant defense mechanisms, is implicated in the pathogenesis of both IBDs and neurodegenerative diseases [ 43 ].…”
Section: Is Neurodegeneration An Extraintestinal Manifestation Of Ibds?mentioning
confidence: 99%
See 1 more Smart Citation
“…The gut-brain has a two-way regulatory function in nerve, endocrine, immunity, and metabolism, and is related to inflammatory bowel disease, obesity, diabetes, insulin resistance, and other gastrointestinal and metabolic diseases ( 6 ). Microorganisms that colonize the intestine play an indispensable role in brain and gut communication.…”
Section: Introductionmentioning
confidence: 99%